Hi, AI [videorecording (DVD)] - Chalmers, David John, 1966- (Blue Water Content, 2024)
With an AI, you have to keep your sentences short and to the point. This piece of advice is given to Chuck as he's picking up his robot partner Harmony fresh from the factory. In Tokyo, Grandma Sakurai is given the cute robot Pepper, so that she feels less lonely. How will robots and artificial intelligence change our lives? This stunning emotional documentary shows us tomorrow's world today. Includes spoken Japanese dialogue with English subtitles.